The secreted Theileria annulata Ta9 protein contributes to activation of the AP-1 transcription factor - Unlu, Ahmet Hakan (PLoS One, 2018)
Theileria annulata is an obligate intracellular protozoan parasite of the phylum Apicomplexa. Theileria sporozoites invade bovine leukocytes and develop into a multinucleate syncytial macroschizont that causes uncontrolled proliferation and dissemination of infected and transformed leukocytes. Activator protein 1 (AP-1) is a transcription factor driving expression of genes involved in proliferation and dissemination and is therefore a key player in Theileria-induced leukocytes transformation. Ta9 possesses a signal peptide allowing it to be secreted into the infected leukocyte cytosol and be presented to CD8 T cells in the context of MHC class I. First, we confirmed that Ta9 is secreted into the infected leukocyte cytosol, and then we generated truncated versions of GFP-tagged Ta9 and tested their ability to activate AP-1 in non-infected HEK293T human kidney embryo cells. The ability to activate AP-1-driven transcription was found to reside in the C-terminal 100 amino acids of Ta9 distant to the N-terminally located epitopes recognised by CD8+ T cells. Secreted Ta9 has therefore, not only the ability to stimulate CD8+ T cells, but also the potential to activate AP-1-driven transcription and contribute to T. annulata-induced leukocyte transformation.